Diet and sex inequities in ischemic heart disease mortality across Europe: findings from the global burden of disease study - Bugiardini, Raffaele; Rahaman, Tania; Manfrini, Olivia; Maas, Angela; Bergami, Maria; Badimon, Lina; Mendieta, Guiomar; Vavlukis, Marija; Merkely, Bela; Vasiljevic, Zorana; Gale, Chris P; Gulati, Martha; et al. (Oxford University Press (OUP), 2025)
Aims Sex differences in ischemic heart disease (IHD) mortality remain underexplored from a population-level case fatality perspective. This study evaluates sex-specific disparities in IHD mortality and risk-attributable causes across 27 European Union (EU) countries using Global Burden of Disease (GBD) 2021 data. Methods and results We calculated age-standardized mortality rates (ASMRs), prevalence rates (ASPRs), and mortality-to-prevalence ratios (MPRs) as a proxy for population-level case fatality. To quantify mortality attributable to specific exposures among individuals with IHD, we derived a case fatality index (CFI) by normalizing risk-attributable ASMRs to ASPRs. Z-scores quantified the magnitude and statistical significance of sex differences in MPRs and CFIs (|Z| ≥ 1.96 = P < 0.05; |Z| ≥ 2.58 = P < 0.01). From 2011 to 2021, IHD ASMRs declined by 24.0% in men and 19.1% in women. In 2011, 12 countries showed significantly higher MPRs in women than men. By 2021, Austria (MPR 6.0% vs. 3.6%), Greece (9.4% vs. 5.3%), and Malta (9.3% vs. 4.2%) remained outliers, with Z-scores >2.58 (P < 0.01). CFIs showed that women in these countries faced 40 to 60% higher mortality burdens from hypertension, hyperglycemia, and poor dietary intake. Low intake of omega-3 fatty acids, fibers, vegetables, and nuts/seeds accounted for the largest dietary disparities. Conclusion Despite declining IHD mortality rates, Austria, Greece, and Malta continue to exhibit significant sex disparities, with women experiencing disproportionately higher case fatality. These disparities are largely driven by modifiable cardiometabolic and dietary risks, underscoring the need for sex-specific, regionally tailored prevention strategies.
This is a paper on the role of Sex differences in ischemic heart disease (IHD) mortality. Despite declining IHD mortality rates, Austria, Greece, and Malta continue to exhibit significant sex disparities, with women experiencing disproportionately higher case fatality. These disparities are largely driven by modifiable cardiometabolic and dietary risks, underscoring the need for sex-specific, regionally tailored prevention strategies.
Keywords: Deaths; Diet; Europe; Ischemic heart disease; Risk factors; Sex differences.